Editorial: Wishful thinking - Maldonado, George (BioMed Central, 2004)
As a supplement to our lead editorial, the editors of the new journal, Epidemiologic Perspectives & Innovations, provide a partial list of specific analyses and topic areas they would like to see submitted to the journal.